ELECTRICITY TARIFFS IN GEORGIA - Maka Jishkariani (World Science, 2019)
Article discusses electricity tariff setting methods, such as: «Rate of Return Regulation», «Price Cup Regulation», «Return Assets Base (RAB)» and «Cost Plus». Meet the interests of electricity producers and consumers are one of the indicators of the health of the electricity sector. At present, the Georgian electricity market is striving to harmonize with EU standards and established electricity tariff methodology should be use the best method to encourage investors to invest in the field and expand their infrastructure while ensuring the reliability and efficiency of electricity supply.